Viscosity-reduced C80-grade concrete and preparation method thereof
By using special polycarboxylic acid water reducers and tea saponin in high-strength concrete, a water film layer and a foam stabilizing agent are formed in high-strength concrete, the problem of high viscosity of high-strength concrete is solved, and the effects of low viscosity, high toughness and high flowability are achieved, and the construction efficiency and application scope are improved.
Patent Information
- Application Number
- CN202510299106.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
Due to the excessive gelling material and low water-gluing ratio of existing high-strength concrete, the viscosity and fluidity of fresh concrete are high, which seriously affects construction efficiency and application promotion.
Polycarboxylic acid water reducing agent is used, and its polymerized monomer includes alkenyl dipolymer ether macromonomer and phenyl acrylate derivative. By adjusting the monomer ratio, a thicker water film layer is formed between cement and blending material, the viscosity of the concrete is reduced, and the use of tea saponin and nonylphenol polyoxyethylene ether is improved to improve the toughness and fluidity of the concrete.
It has achieved the reduction of the viscosity of concrete, improved its fluidity and toughness, improved construction efficiency and application range, and specifically manifested as excellent mechanical strength and toughness.
Smart Images

Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and particularly relates to a reduced-viscosity C80 grade concrete and a preparation method thereof. Background Art
[0002] With the rapid development of the construction industry, building structures are gradually developing towards super-high-rise, lightweight and large-span directions, which puts forward higher requirements on the mechanical properties and construction performance of concrete, and also greatly promotes the development of concrete pumping technology. High-strength concrete structures have higher bearing capacity. When the design load is the same, a smaller cross-sectional area can be used to better adapt to various requirements of building design. At the same time, it can reduce the deadweight of the concrete structure. Therefore, it has attracted much attention. For example, patent CN113264728B discloses a high-strength and high-toughness concrete and its preparation method. The raw materials for the preparation of high-strength and high-toughness concrete are measured by weight, including 150-170 parts of water, 200-250 parts of cement, 200-250 parts of coarse aggregate, 350-400 parts of fine aggregate, 40-70 parts of ultrafine powder, 50-70 parts of structural modification material, 10-20 parts of cellulose and 10-25 parts of chemical additives. Patent CN113880521B discloses a high-strength impermeable concrete and a production method thereof, which is mainly made of the following raw materials in parts by weight: 650-780 parts of aggregate, 500-600 parts of sand, 280-400 parts of cement, 80-120 parts of fly ash, 100-200 parts of water, 25-40 parts of water reducer, 75-90 parts of admixture, and 80-150 parts of impermeability agent; the impermeability agent is composed of the sum of the mass of polyethylene oxide and dehydrated sorbitan fatty acid ester and nickel salt in a mass ratio of (2.5-4):(4-7), and the admixture is at least two of tuff powder, limestone powder, and quartz powder.
[0003] The above is high-strength concrete with high strength. In order to make the concrete high-strength, a large amount of cementitious materials and a low water-cement ratio are used, which leads to high viscosity and reduced fluidity of the freshly mixed concrete, which reduces the pumping performance of the concrete, seriously affects the construction efficiency, and limits its application and promotion. Therefore, it is necessary to develop a low-viscosity high-strength concrete. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a C80 grade concrete with reduced viscosity and a preparation method thereof. The polymerization monomer of the polycarboxylic acid water-reducing agent used includes a highly hydrophilic alkenyl dipolyether macromonomer, which is first prepared by reacting 1,3-diglycidyl ether glycerol and acryloyl chloride derivatives to prepare unsaturated diglycidyl ether, and then the unsaturated diglycidyl ether is reacted with O-(2-aminoethyl) polyethylene glycol to obtain the concrete. The monomer phenyl acrylate derivative has a hydrophobic phenyl group. Adjusting the relative ratio of the two monomers is beneficial to forming a thicker water film layer between cement and admixture cementitious particles, thereby reducing the viscosity of the concrete.
[0005] In order to achieve the above purpose, the following technical solutions are adopted: A viscosity-reducing C80 grade concrete comprises the following raw materials: 350-400 parts by weight of cement, 100-150 parts by weight of admixture, 600-700 parts by weight of fine aggregate, 850-1000 parts by weight of coarse aggregate, 5-8 parts by weight of polycarboxylate water-reducing agent solution, 2-4 parts by weight of nonylphenol polyoxyethylene ether, 2-4 parts by weight of tea saponin, 25-30 parts by weight of toughening agent and water, wherein the mass ratio of the total mass of cement and admixture to water is 1:0.2-0.28; the solid content of the polycarboxylate water-reducing agent solution is 35-45wt%; the polycarboxylate water-reducing agent is copolymerized by alkenyl polyether macromonomer, alkenyl dimer ether macromonomer, unsaturated acid derivative and phenyl acrylate derivative in a mass ratio of 70-80:20-30:7-10:5-10; The structural formula of the alkenyl dimer ether macromonomer is shown in the following formula (I): (I); wherein m and n are independently integers between 40 and 80, and R is -CH3 or -H.
[0006] The monosaccharide on the tea saponin molecule has many hydroxyl groups that can form hydrogen bonds with water molecules, so it has strong hydrophilicity. The aglycone in the aglycon group is lipophilic and hydrophobic, so tea saponin belongs to non-ionic surfactants. Tea saponin applied to concrete has the effect of entraining air to produce uniform micro bubbles, improving the toughness and durability of concrete; in addition, because the bubbles also have a lubricating effect, tea saponin can also reduce the viscosity of concrete slurry.
[0007] The polymerized monomer alkenyl dimer macromonomer of polycarboxylic acid water-reducing agent has strong hydrophilicity, which helps to form a thicker water film layer between the cementitious particles mixed with cement and admixtures, thereby reducing the viscosity of concrete. However, the polyether chain produced by the hydrolysis of alkenyl dimer macromonomer has a defoaming effect, resulting in poor toughness of concrete. The use of an appropriate amount of foam stabilizer nonylphenol polyoxyethylene ether can improve the toughness of the slurry without affecting other properties of the concrete slurry.
[0008] The alkenyl dimer ether macromonomer is prepared by a method comprising the following steps: 1) Under an inert atmosphere, 1,3-diglycidyl ether glycerol, (meth)acryloyl chloride, an acid binding agent, a polymerization inhibitor, and an organic solvent are added to a reaction kettle, and the temperature is controlled to react. After the reaction is completed, the reaction is filtered and distilled under reduced pressure to obtain unsaturated diglycidyl ether; 2) Under an inert atmosphere, unsaturated diglycidyl ester, O-(2-aminoethyl) polyethylene glycol, an inhibitor, and an organic solvent are mixed uniformly, heated, and reacted at a constant temperature. After the reaction is completed, the mixture is concentrated and separated by gel chromatography to obtain an olefin dimer macromonomer.
[0009] Step 1) The organic solvent is selected from one or a combination of chloroform and petroleum ether. The mass of the organic solvent is 3-5 times the mass of 1,3-diepoxyglyceryl ether glycerol and (meth) acryloyl chloride. The acid binding agent is selected from one or a combination of two or more of triethylamine, N,N-diisopropylethylamine, 2-methylpyridine, and pyridine. The temperature control is controlled at 1-10°C, and the reaction time is 3-5h. The inhibitor is selected from one or a combination of two or more of p-tert-butylphenol, p-hydroxyanisole, and hydroquinone. The molar ratio of (meth) acryloyl chloride, 1,3-diepoxyglyceryl ether glycerol, and acid binding agent is 1:1.1-1.15:1-1.1. The inhibitor is 0.1-0.3wt% of acryloyl chloride derivative.
[0010] Step 2) The number average molecular weight of the O-(2-aminoethyl) polyethylene glycol is 2000-3400. The unsaturated glycidyl ester is selected from one or a combination of glycidyl acrylate and glycidyl methacrylate. The temperature is raised to 60-80°C, and the reaction time is 3-6h. The organic solvent is selected from one or a combination of two or more of DMF, acetone, acetonitrile, DMSO, and tetrahydrofuran. The mobile phase for gel chromatography separation is tetrahydrofuran. The molar ratio of the unsaturated diglycidyl ester to O-(2-aminoethyl) polyethylene glycol is 1:2.1-2.2. The inhibitor is 0.1-0.3wt% of the unsaturated diglycidyl ester. The inhibitor is selected from one or a combination of two or more of p-tert-butylphenol, p-hydroxyanisole, and hydroquinone.
[0011] The alkenyl polyether macromonomer has a number average molecular weight of 2000-2400 and is selected from methyl allyl polyoxyethylene ether, allyl polyoxyethylene ether or a combination of the two.
[0012] The unsaturated acid derivative is selected from one or a combination of two or more of acrylic acid, methacrylic acid, maleic acid, fumaric acid and itaconic acid.
[0013] The phenyl acrylate derivative is selected from one or a combination of two or more of phenyl acrylate, phenyl methacrylate, 2-phenoxyethyl acrylate, 2-phenoxyethyl methacrylate, and 2-phenylethyl methacrylate.
[0014] The polycarboxylate water reducer is prepared by a method comprising the following steps: Under an inert atmosphere, alkenyl polyether macromonomer and alkenyl dimer ether macromonomer are added to a reaction kettle, the temperature is raised and mixed evenly, unsaturated acid derivatives, phenyl acrylate derivatives, initiators, and chain transfer agents are added and mixed evenly, the temperature is raised again and the reaction is carried out at a constant temperature. After the reaction is completed, the reaction is cooled to room temperature, the pH is adjusted, and water is added to adjust the solid content to obtain a polycarboxylic acid water-reducing agent solution.
[0015] The first heating is to 30-50°C. The second heating is to 60-80°C, and the reaction time is 3-5h. The amount of the initiator is 1-3wt% of the mass sum of the alkenyl polyether macromonomer, alkenyl dimer ether macromonomer, unsaturated acid derivatives, and phenyl acrylate derivatives. The initiator is selected from one or a combination of two or more of BPO, isophenyl hydroperoxide, and tert-butyl hydroperoxide. The chain transfer agent is selected from one or a combination of two of mercaptoethanol and dodecyl mercaptan. The amount of the chain transfer agent is 0.5-0.8wt% of the mass sum of the alkenyl polyether macromonomer, alkenyl dimer ether macromonomer, unsaturated acid derivatives, and phenyl acrylate derivatives. The pH is adjusted to 7-9 with alkali solution, and the alkali solution is selected from one or a combination of two or more of sodium hydroxide solution, sodium carbonate solution, and sodium bicarbonate solution. The solid content is adjusted to 35-45wt% by adding water.
[0016] The nonylphenol polyoxyethylene ether is selected from one or a combination of two or more of NP-10, NP-16 and NP-20.
[0017] The toughening agent is a liquid rubber-coated inorganic filler, which is prepared by a method comprising the following steps: Inorganic filler, carboxyl-terminated polybutadiene liquid rubber, organic solvent and ball milling medium are added into a ball mill, ball milling is performed to obtain ball milling slurry, and the toughening agent is obtained by filtering and drying.
[0018] The ball milling medium is zirconium oxide beads with a particle size of 0.1mm-0.5mm. The rotation speed of the ball mill is 200-800r / min. The ball milling time is 3-5h. The mass ratio of the inorganic filler and the liquid rubber to the ball milling medium is 1:20-25. The mass ratio of the inorganic filler, the liquid rubber and the organic solvent is 5:0.4-0.5:10-15. The organic solvent is selected from one or a combination of two or more of toluene, benzene, dichloromethane, methyl ethyl ketone and ethyl acetate. The ball milling temperature is 25-50°C. The drying is drying at 60-80°C and a vacuum degree of 0.01-0.1MPa for 1-3h.
[0019] The liquid rubber has a number average molecular weight of 3000-5000 and is selected from one or a combination of two or more of carboxyl-terminated polybutadiene liquid rubber, hydroxyl-terminated polybutadiene liquid rubber and polybutadiene liquid rubber.
[0020] The inorganic filler has an average particle size of 50-100 nm and is selected from one or a combination of two or more of silicon dioxide, calcium carbonate, talcum powder and magnesium carbonate.
[0021] The cement is silicate cement with a strength grade of 42.5 to 52.5.
[0022] The fine aggregate is quartz sand with a fineness modulus of 3.0-2.3.
[0023] The coarse aggregate is continuously graded crushed stone with a particle size of 5-20 mm.
[0024] The admixture is selected from fly ash, mineral powder or a combination of the two.
[0025] The admixture is a mixture of fly ash and mineral powder in a mass ratio of 1:2-5.
[0026] The fly ash is selected from one of Class I fly ash and Class II fly ash, or a combination of the two.
[0027] The mineral powder is selected from one of S105 grade mineral powder, S95 grade mineral powder, S75 grade mineral powder or a combination of two thereof.
[0028] The present invention also provides a method for preparing the above-mentioned reduced viscosity C80 grade concrete, comprising the following steps: The cement, admixture, polycarboxylic acid water-reducing agent solution, nonylphenol polyoxyethylene ether, tea saponin, toughening agent and water are uniformly mixed to obtain slurry, and the coarse aggregate and fine aggregate are added to the slurry and mixed uniformly to obtain the reduced-viscosity C80 grade concrete.
[0029] Compared with the prior art, the present invention has the following beneficial effects: The polycarboxylic acid water-reducing agent of the present invention is prepared by copolymerizing alkenyl polyether macromonomer, alkenyl dimer ether macromonomer, unsaturated acid derivative and phenyl acrylate derivative through bulk polymerization. The alkenyl dimer ether macromonomer is a kind of alkenyl dimer ether macromonomer with strong hydrophilicity. The unsaturated diglycidyl ether is first prepared by reacting 1,3-diglycidyl ether glycerol and acryloyl chloride derivative, and then the unsaturated diglycidyl ether is reacted with O-(2-aminoethyl) polyethylene glycol to obtain the polycarboxylic acid water-reducing agent. The monomer phenyl acrylate derivative has a hydrophobic phenyl group. Adjusting the relative proportion of the two monomers is beneficial to forming a thicker water film layer between cement and admixture gelling particles, thereby reducing the viscosity of the concrete. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0031] O-(2-aminoethyl)polyethylene glycol with a number average molecular weight of 2000 and a product number of H917140 was purchased from MacLean.
[0032] O-(2-aminoethyl)polyethylene glycol with a number average molecular weight of 3400 and a product number of H917141 was purchased from MacLean.
[0033] Allyl polyoxyethylene ether with a number average molecular weight of APEG2400 was purchased from Wuhan Xinxin Jiali Biotechnology Co., Ltd.
[0034] Continuously graded gravel with a particle size of 5-20 mm was purchased from Huzhou Xinkaiyuan Gravel Co., Ltd.
[0035] Quartz sand with a fineness modulus of 2.6 was purchased from Fengyang Jihui Quartz Sand Co., Ltd.
[0036] Nano-silicon dioxide DK-SiO2-60 with an average particle size of 60 nm was purchased from Zhongke Jinyan (Beijing) Technology Co., Ltd.
[0037] Type I carboxyl-terminated polybutadiene liquid rubber has a number average molecular weight of 5000 and was purchased from Tianyuan Aerospace Materials.
[0038] Example 1 1) Under nitrogen atmosphere, 1.1 mol of 1,3-diglycidyl ether glycerol, 1 mol of acryloyl chloride, 1 mol of triethylamine, 0.1 wt% of hydroquinone by weight of acryloyl chloride, and 1,3-diglycidyl ether glycerol and acryloyl chloride and 3 times of chloroform were added to a reactor, and the temperature was controlled at 10°C for 3 hours. After the reaction was completed, solid triethylamine hydrochloride was removed by filtration and distilled under reduced pressure to obtain unsaturated diglycidyl ether; 2) Under nitrogen atmosphere, 1 mol of unsaturated diglycidyl ester, 2.1 mol of O-(2-aminoethyl) polyethylene glycol with product number H917141, 0.2 wt% of hydroquinone by weight of unsaturated diglycidyl ester, the weight of unsaturated diglycidyl ester and O-(2-aminoethyl) polyethylene glycol and 3 times of tetrahydrofuran were mixed and uniformly heated to 60°C and reacted at a constant temperature for 6 hours. After the reaction was completed, the mixture was concentrated and separated by gel chromatography with tetrahydrofuran as the mobile phase to obtain the alkenyl dimer macromonomer.
[0039] 3) Under an inert atmosphere, add 80g APEG2400 and 30g alkenyl dimer monomer to the reactor, heat to 50°C and mix evenly, add 10g maleic acid, 10g phenyl acrylate, four polymerized monomers and 3wt% BPO, four polymerized monomers and 0.8wt% mercaptoethanol and mix evenly, heat to 60°C and react at a constant temperature, cool to room temperature after 5h of reaction, adjust the pH to 7 with 32wt% sodium hydroxide solution, add water to adjust the solid content to 45wt%, and obtain a polycarboxylic acid water reducer solution.
[0040] 4) Add 50g DK-SiO2-60, 5g type I carboxyl-terminated polybutadiene liquid rubber, 150g toluene, and zirconia beads with a particle size of 0.2mm into a ball mill with a ball-to-material ratio of 20:1. Ball mill at 30℃ for 5h to obtain ball milled slurry, filter it, and dry it at 60℃ and a vacuum degree of 0.08MPa to obtain the toughening agent.
[0041] 5) 400 parts by mass of silicate cement with a strength grade of 52.5, 150 parts by mass of an admixture prepared by mixing grade I fly ash and grade S95 mineral powder in a mass ratio of 1:5, 8 parts by mass of polycarboxylic acid water-reducing agent solution, 4 parts by mass of nonylphenol polyoxyethylene ether NP-20, 4 parts by mass of tea saponin, 30 parts by mass of toughening agent, the mass of silicate cement and the admixture and 0.28 times of water were mixed to obtain a slurry, and 1000 parts by mass of crushed stone and 700 parts by mass of quartz sand were added to the slurry and mixed to obtain a reduced viscosity C80 grade concrete.
[0042] Example 2 The rest is the same as Example 1, except that in step 3), the amount of alkenyl dimer ether macromonomer used is 20 g.
[0043] Example 3 The rest is the same as Example 1, except that in step 3), the amount of phenyl acrylate used is 5 g.
[0044] Example 4 The rest is the same as Example 1, except that in step 3), an equimolar amount of O-(2-aminoethyl) polyethylene glycol with the product number H917140 is used to replace O-(2-aminoethyl) polyethylene glycol with the product number H917141.
[0045] Example 5 The rest is the same as Example 1, except that in step 5), the amount of nonylphenol polyoxyethylene ether NP-20 used is 2 parts by mass.
[0046] Example 6 The rest is the same as Example 1, except that in step 5), the amount of the polycarboxylate water-reducing agent solution is 5 parts by mass.
[0047] Example 7 The rest is the same as Example 1, except that in step 5), the amount of tea saponin used is 2 parts by mass.
[0048] Example 8 1) Under nitrogen atmosphere, 1.15 mol of 1,3-diglycidyl ether glycerol, 1 mol of acryloyl chloride, 1 mol of triethylamine, 0.1 wt% of hydroquinone by weight of acryloyl chloride, and 3 times the weight of chloroform were added to a reactor, and the temperature was controlled at 10°C for 3 hours. After the reaction was completed, solid triethylamine hydrochloride was removed by filtration and distilled under reduced pressure to obtain unsaturated diglycidyl ether; 2) Under nitrogen atmosphere, 1 mol of unsaturated diglycidyl ester, 2.1 mol of O-(2-aminoethyl) polyethylene glycol with product number H917140, 0.2 wt% of hydroquinone by weight of unsaturated diglycidyl ester, the weight of unsaturated diglycidyl ester and O-(2-aminoethyl) polyethylene glycol and 3 times of tetrahydrofuran were mixed and uniformly heated to 60°C and reacted at a constant temperature for 6 hours. After the reaction was completed, the mixture was concentrated and separated by gel chromatography with tetrahydrofuran as the mobile phase to obtain the alkenyl dimer macromonomer.
[0049] 3) Under an inert atmosphere, add 80g APEG2400 and 30g alkenyl dimer monomer to the reactor, heat to 50°C and mix evenly, add 7g maleic acid, 10g 2-phenylethyl methacrylate, four polymerized monomers and 3wt% BPO, four polymerized monomers and 0.8wt% mercaptoethanol and mix evenly, heat to 60°C again and react at a constant temperature. After 5h of reaction, cool to room temperature, adjust the pH to 7 with 32wt% sodium hydroxide solution, add water to adjust the solid content to 45wt%, and obtain a polycarboxylic acid water reducer solution.
[0050] 4) Add 50g DK-SiO2-60, 5g type I carboxyl-terminated polybutadiene liquid rubber, 150g toluene, and zirconia beads with a particle size of 0.2mm into a ball mill with a ball-to-material ratio of 20:1. Ball mill at 30℃ for 5h to obtain ball milled slurry, filter it, and dry it at 60℃ and a vacuum degree of 0.08MPa to obtain the toughening agent.
[0051] 5) 350 parts by mass of silicate cement with a strength grade of 52.5, 150 parts by mass of an admixture prepared by mixing grade I fly ash and grade S95 mineral powder in a mass ratio of 1:5, 5 parts by mass of polycarboxylic acid water-reducing agent solution, 2 parts by mass of nonylphenol polyoxyethylene ether NP-20, 4 parts by mass of tea saponin, 30 parts by mass of toughening agent, the mass of silicate cement and the admixture and 0.28 times of water were mixed to obtain a slurry, and 850 parts by mass of crushed stone and 600 parts by mass of quartz sand were added to the slurry and mixed to obtain a reduced viscosity C80 grade concrete.
[0052] Comparative Example 1 The rest is the same as Example 1, except that in step 5), an equal amount of octylphenol polyoxyethylene ether TX-25 is used instead of nonylphenol polyoxyethylene ether NP-20.
[0053] Comparative Example 2 The rest is the same as Example 1, except that in step 1), an equal mass of APEG2400 is used to replace the alkenyl dimer ether macromonomer.
[0054] Comparative Example 3 The rest is the same as Example 1, except that in step 5), an equal mass of dodecylbenzene sulfonate air-entraining agent is used to replace tea saponin.
[0055] The concrete prepared in the above examples and comparative examples was subjected to the following performance tests: Flexural strength: Standard curing for 28 days, tested in accordance with GB / T50081-2002 Test method for mechanical properties of ordinary concrete.
[0056] Concrete viscosity: Referring to the standard JGJ281-2012 Technical Specification for Application of High-Strength Concrete, the emptying time t of the concrete mixture is tested by using an inverted slump bucket to evaluate the viscosity of the concrete.
[0057] Table 1 Performance test results
[0058] It can be seen from Table 1 that the viscosity-reduced C80 grade concrete prepared by the present invention has excellent mechanical strength and toughness.
[0059] It can be seen from the emptying time t of the inverted slump bucket of Examples 1-4 and Comparative Example 2 that the polycarboxylate water-reducing agent of the present invention has an excellent viscosity reduction effect. It can be seen from the emptying time t of the inverted slump bucket of Example 1, Example 5, and Comparative Example 1 that the use of the foam stabilizer nonylphenol polyoxyethylene ether NP-20 has little effect on the viscosity of the concrete; but as time goes on, the alkenyl dimer macromonomer hydrolyzes in the alkaline slurry to produce polyether segments with defoaming effects, and the flexural strength of the concrete after the final hardening of Comparative Example 1 with the addition of non-nonylphenol polyoxyethylene ether is low; it can be seen from Example 1, Example 7, and Comparative Example 3 that the use of tea saponin is beneficial to reducing the viscosity of the concrete and improving the fluidity. If the high-efficiency dodecylbenzene sulfonate air-entraining agent is replaced, although a large number of bubbles can be generated to reduce the viscosity, the excessive air entrainment reduces the flexural strength, which is speculated to cause the uneven size and distribution of bubbles inside the concrete, and the toughness is greatly reduced. It can be seen from this that in order to obtain concrete with both high toughness and low viscosity, the prepared polycarboxylic acid water reducer needs to be used together with the foam stabilizer nonylphenol polyoxyethylene ether and tea saponin. There is a synergistic effect between them, and together they can obtain concrete with both high toughness and low viscosity.
Claims
1. A C80 grade concrete with reduced viscosity, characterized in that: The invention comprises the following raw materials: 350-400 parts by weight of cement, 100-150 parts by weight of admixture, 600-700 parts by weight of fine aggregate, 850-1000 parts by weight of coarse aggregate, 5-8 parts by weight of polycarboxylate water-reducing agent solution, 2-4 parts by weight of nonylphenol polyoxyethylene ether, 2-4 parts by weight of tea saponin, 25-30 parts by weight of toughening agent and water, wherein the mass ratio of the total mass of cement and admixture to water is 1:0.2-0.28; the solid content of the polycarboxylate water-reducing agent solution is 35-45wt%; the polycarboxylate water-reducing agent is copolymerized by alkenyl polyether macromonomer, alkenyl dimer ether macromonomer, unsaturated acid derivative and phenyl acrylate derivative in a mass ratio of 70-80:20-30:7-10:5-10; The structural formula of the alkenyl dimer ether macromonomer is shown in the following formula (I): (I); wherein m and n are independently integers between 40 and 80, and R is -CH3 or -H.
2. The viscosity-reduced C80 grade concrete according to claim 1, characterized in that: The alkenyl dimer ether macromonomer is prepared by a method comprising the following steps: 1) Under an inert atmosphere, 1,3-diglycidyl ether glycerol, (meth)acryloyl chloride, an acid binding agent, a polymerization inhibitor, and an organic solvent are added to a reaction kettle, and the temperature is controlled to react. After the reaction is completed, the reaction is filtered and distilled under reduced pressure to obtain unsaturated diglycidyl ether; 2) Under an inert atmosphere, unsaturated diglycidyl ester, O-(2-aminoethyl) polyethylene glycol, an inhibitor, and an organic solvent are mixed uniformly, heated, and reacted at a constant temperature. After the reaction is completed, the mixture is concentrated and separated by gel chromatography to obtain an olefin dimer macromonomer.
3. The viscosity-reduced C80 grade concrete according to claim 2, characterized in that: In step 1), the molar ratio of (meth)acryloyl chloride, 1,3-diepoxyglyceryl ether glycerol and acid binding agent is 1:1.1-1.15:1-1.
1.
4. The viscosity-reduced C80 grade concrete according to claim 2, characterized in that: Step 1) The temperature is controlled at 1-10°C, and the reaction time is 3-5h; the inhibitor is 0.1-0.3wt% of acryloyl chloride derivative.
5. The viscosity-reduced C80 grade concrete according to claim 2, characterized in that: Step 2) The molar ratio of the unsaturated diglycidyl ester to O-(2-aminoethyl) polyethylene glycol is 1:2.1-2.2; the number average molecular weight of the O-(2-aminoethyl) polyethylene glycol is 2000-3400; the unsaturated glycidyl ester is selected from one or a combination of glycidyl acrylate and glycidyl methacrylate.
6. The viscosity-reduced C80 grade concrete according to claim 2, characterized in that: Step 2) The temperature is raised to 60-80°C and the reaction time is 3-6h.
7. The viscosity-reduced C80 grade concrete according to claim 1, characterized in that: The alkenyl polyether macromonomer has a number average molecular weight of 2000-2400 and is selected from one or a combination of methyl allyl polyoxyethylene ether and allyl polyoxyethylene ether; the unsaturated acid derivative is selected from one or a combination of two or more of acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid; the phenyl acrylate derivative is selected from one or a combination of two or more of phenyl acrylate, phenyl methacrylate, 2-phenoxyethyl acrylate, 2-phenoxyethyl methacrylate, and 2-phenylethyl methacrylate; the nonylphenol polyoxyethylene ether is selected from one or a combination of two or more of NP-10, NP-16, and NP-20.
8. The viscosity-reduced C80 grade concrete according to claim 1, characterized in that: The polycarboxylate water reducer is prepared by a method comprising the following steps: Under an inert atmosphere, alkenyl polyether macromonomer and alkenyl dimer ether macromonomer are added to a reaction kettle, the temperature is raised and mixed evenly, unsaturated acid derivatives, phenyl acrylate derivatives, initiators, and chain transfer agents are added and mixed evenly, the temperature is raised again and the reaction is carried out at a constant temperature. After the reaction is completed, the reaction is cooled to room temperature, the pH is adjusted, and water is added to adjust the solid content to obtain a polycarboxylic acid water-reducing agent solution.
9. The viscosity-reduced C80 grade concrete according to claim 1, characterized in that: The toughening agent is a liquid rubber-coated inorganic filler, which is prepared by a method comprising the following steps: Inorganic filler, carboxyl-terminated polybutadiene liquid rubber, organic solvent and ball milling medium are added into a ball mill, ball milling is performed to obtain ball milling slurry, and the toughening agent is obtained by filtering and drying.
10. The method for preparing the reduced viscosity C80 grade concrete according to any one of claims 1 to 9, characterized in that: The steps include: The cement, admixture, polycarboxylic acid water-reducing agent solution, nonylphenol polyoxyethylene ether, tea saponin, toughening agent and water are uniformly mixed to obtain slurry, and the coarse aggregate and fine aggregate are added to the slurry and mixed uniformly to obtain the reduced-viscosity C80 grade concrete.
Citation Information
Patent Citations
A high-strength impermeable concrete and its production method
CN113880521B
BE699610A
Alkene based amine polyether and method of preparing the same
CN101367928A
Long-chain branch end group esterified and modified polycarboxylate water reducer and preparation method
CN107446089A
Co-polymer containing double polyoxyethylene branch structures and production and application of co-polymer containing double polyoxyethylene branch structures
CN110746551A